Hubungan antara personal hygiene dengan infeksi telur cacing usus (soil transmitted helminths) pada petani sayur di kabupaten gianyar: The relationship between personal hygiene and soil transmitted helminths in vegetable farmers in gianyar district - Yani, Ida; Putri, Ni Luh Nova Dilisca Dwi; Abadi, M. Fairuz (Stikes Wira Medika Bali, 2021)
Soil Transmitted Helminths (STH) are intestinal nematode worms that infect humans who ingest their eggs via the faecal-oral route. Soil Transmitted Helminths (STH) infection is transmitted through eggs and larvae found in human feces which then contaminate the soil in environmental areas that have poor sanitation. The impact caused by worms includes malnutrition, growth and development disorders and cognitive disorders in children, and in adults it can reduce work productivity. The incidence of worms is found mainly in people living in rural areas, especially farmers. STH transmission to vegetable farmers occurs through water and sludge used in vegetable cultivation. STH prevalence is supported by suitable natural conditions, personal hygiene and low environmental sanitation, especially in the vegetable farming environment. This study aims to determine the relationship between personal hygiene and intestinal worm egg infection (Soil Transmitted Helmint) vegetable farmers in Gianyar Regency. The type of research used in this study is a descriptive correlative study with a cross sectional study approach which aims to determine the relationship between personal hygiene and intestinal worm infection (Soil Transmitted Helmint) in vegetable farmers in Gianyar Regency. The results showed that the personal hygiene condition of vegetable farmers in Gianyar Regency was poor (83.3%) and the incidence of worm infection in vegetable farmers in Gianyar Regency was 20%. There is no relationship between personal hygiene personal hygiene with intestinal worm egg infections (Soil Transmitted Helmint) in vegetable farmers in Gianyar Regency (p-value> 0.05).